Risk Factors of Coronary Heart Disease among Bank Employees of Belgaum City - Cross-Sectional Study - H.R. Shivaramakrishna; A.S Wantamutte; H.N Sangolli; M.D Mallapur (Al Ameen Medical College, 2010)
Background: Bank employees, with their resources and infrastructure, are ideal for increasing awareness and initiating preventive activities for the control of coronary heart disease (CHD). However, there are no reliable estimates of CHD risk factor burden, or of its awareness and treatment status among bank employees. The study intends to evaluate the prevalence of risk factors of CHD among bank employees of Belgaum city. Objectives: To estimate the prevalence of risk factors of CHD and to assess the knowledge regarding risk factors of CHD among bank employees. Methodology: It was a cross-sectional study for a period of one month. The study population consisted of bank employees working in various banks in Belgaum city. Results: The prevalence of risk factors of CHD was as follows: hypertension 31%, diabetes 21%, high serum total cholesterol 29%, high triglycerides 39%, high LDL cholesterol 19.3%, low HDL cholesterol 17.7%, smoking 26%, sedentary habits 44%, positive family history 12%, overweight / obesity (BMI >25 kg/m2) 33% and 26% of the study subjects had truncal obesity. Among these, 55% of the study subjects had at least two of these risk factors. Conclusion: The present study shows a disturbing burden of coronary risk factors in the study population. There is an urgent need to undertake population based measures to reverse the trend.